SOSIALISASI KARAKTER KEWIRAUSAHAAN DAN DIGITALISASI PADA SMA NEGERI I KAWAY XVI ACEH BARAT - Chairiyaton Chairiyaton; Leli Putri Ansari; Jun Musnadi Is; Cut Devi Maulidasari; Nabila Hilmy Zhafira (Universitas Teuku Umar, 2022)
High school students are part of generation Z or digital native where their daily lives are very familiar with digitalisation technology. The negative impact of technology and the contribution of unemployment rates to senior high school equivalents is also a big homework for West Aceh District and most of the city districts in Indonesia. Starting from this through community service programs intend to take an active role in efforts to reduce negative impacts and reduce numbers unemployment through socialization activities character of entrepreneurship and digitalization. Activities carried out through socialization, question and answer by the method Presentation and discussion. This method was chosen so that the writer as a speaker can convey important concepts to be understood and mastered by participants.The result of this program is understanding how to grow entrepreneurial character through digital technology so that it becomes a young entrepreneur with creative power, innovative observant in seeing, finding and exploiting business opportunities to play a role in reducing unemployment. Motivate and understand how to be the generation that controls technology rather than technology